"Good" and "Bad" Workers and the Collapse of the Expected Life Course: The Postwar Working Class in Detroit (USA) and Łódź (Poland), 1940s–1980s. Issue 1 (February 2021) - Zysiak, Agata
Two former industrial giants on opposite sides of the globe—the well-known and extensively studied city of Detroit (USA) and the lesser-known but regionally important city of Łódź (Poland)—developed in historically differing economic and political circumstances but have much in common. In both cases, postwar prosperity brought the working class to the center of the social imaginary, resulting in the emergence of a corporate welfare state on one side of the Atlantic Ocean and a socialist one on the other. Thus, two "workers' El Dorados" were based on almost opposite lifestyles, values and models of society, and each lasted for no more than one generation. Changes in industrial structures and locations, the inflexibility of the mono-industrial giants, and a general shift to late capitalism and the post-Fordist mode of production affected both cities. Workers' biographies were experienced through the primacy of work as a means of individual, social, and state reproduction. Factory work offered a device for the allocation of social worth and welfare benefits across time in both contexts. The latter is examined by the construct of a "good worker" and the creation of an imagined, expected life course in the postwar welfare projects, as well as the generational division of workers.